The Arabidopsis NRT1.1 transporter participates in the signaling pathway triggering root colonization of nitrate-rich patches - Remans, Tony (National Academy of Sciences, 2006)
Localized proliferation of lateral roots in NO(3)(−)-rich patches is a striking example of the nutrient-induced plasticity of root development. In Arabidopsis, NO(3)(−) stimulation of lateral root elongation is apparently under the control of a NO(3)(−)-signaling pathway involving the ANR1 transcription factor. ANR1 is thought to transduce the NO(3)(−) signal internally, but the upstream NO(3)(−) sensing system is unknown. Here, we show that mutants of the NRT1.1 nitrate transporter display a strongly decreased root colonization of NO(3)(−)-rich patches, resulting from reduced lateral root elongation. This phenotype is not due to lower specific NO(3)(−) uptake activity in the mutants and is not suppressed when the NO(3)(−)-rich patch is supplemented with an alternative N source but is associated with dramatically decreased ANR1 expression. These results show that NRT1.1 promotes localized root proliferation independently of any nutritional effect and indicate a role in the ANR1-dependent NO(3)(−) signaling pathway, either as a NO(3)(−) sensor or as a facilitator of NO(3)(−) influx into NO(3)(−)-sensing cells. Consistent with this model, the NRT1.1 and ANR1 promoters both directed reporter gene expression in root primordia and root tips. The inability of NRT1.1-deficient mutants to promote increased lateral root proliferation in the NO(3)(−)-rich zone impairs the efficient acquisition of NO(3)(−) and leads to slower plant growth. We conclude that NRT1.1, which is localized at the forefront of soil exploration by the roots, is a key component of the NO(3)(−)-sensing system that enables the plant to detect and exploit NO(3)(−)-rich soil patches.